Hubungan Usia dengan Tekanan Darah Sistolik dan Diastolik Lansia Hipertensi - Ruslang Ruslang; Nirmawati Darwis; Anugerah Yanuar Azis; Yammar Yammar; Salmawati B (Journal Research of Nursing & Midwifery (JRNM), 2025)
Hypertension is one of the most common diseases suffered by the elderly. Hypertension is also referred to as “the silent disease” because there are no signs or symptoms that can be seen from the outside. The development of hypertension runs slowly, but is potentially very dangerous. In the initial survey conducted by the researcher, it was obtained data on the number of elderly people who experienced the most hypertension in Nepo Village. The purpose of this study was to determine the correlation between age and blood pressure of elderly hypertension. The method used in this study uses a descriptive method with a quantitative approach. The population in this study were 38 elderly people. The sampling technique used Accidental sampling with a total sample of 27 people according to the inclusion and exclusion criteria. Measurement of blood pressure using a Sphygmomanomater or Tensimeter (blood pressure measuring device), the use of an observation sheet to record the results of measuring the blood pressure of the elderly and informed consent as a statement of the elderly's willingness to become respondents which contains general elderly data such as identity. The results of statistical tests using the chi-square test obtained a correlation of age with systolic blood pressure p 0.046 <α 0.05 and a correlation of age with diastolic blood pressure p 0.044 <α 0.05, so it can be concluded that there is a correlation between age and blood pressure in elderly hypertension.